Effect of Mobile Banking on Financial Inclusion Among Commercial Banks in Kenya - Isabwa, Harwood Kajirwa (International Journal of Business, Management and Economics, 2021)
Mobile banking is a precursor for the realization of financial inclusion among commercial banks in Kenya. The study's main objective was to determine the effect of mobile banking on financial inclusion among commercial banks in Kenya. The study adopted a positivism research philosophy. The study adopted an expo-facto research design because secondary data was the primary source data. The target population was 43 commercial banks in Kenya. The sample size was 39 commercial banks, but only ten commercial banks were selected because they had the best mobile banking apps. Inferential statistics adopted were; Pearson correlation and regression analysis. The study results revealed that mobile funds transfers significantly affect financial inclusion (β =1.697, p= 0.000). Cash withdrawals via mobile platforms significantly affect financial inclusion (β =1.195, p= 0.000). The study concluded that mobile banking has a significant effect on financial inclusion among commercial banks. In contrast, deposits via mobile platforms have a significant positive effect on financial inclusion (β =.354, p= 0.000). The study recommends that all financial institutions should adopt mobile banking as it helps to achieve financial inclusion. The banking sector should adopt the most appropriate mobile banking strategies to enhance financial inclusion.